Correlation of ICG lymphography and lymphoscintigraphy severity stage in secondary upper limb lymphedema. Issue 11 (November 2020) - Yoon, Jin A; Shin, Myung Jun; Shin, Yong Beom; Kim, Keunyoung; Park, Heeseung; Kang, Taewoo; Kong, In Joo; Kim, Hyojeong; Park, Min Suk; Kim, Joo Hyoung
Summary: Purpose: To examine the correlation between lymphedema severity stages on lymphoscintigraphy and on indocyanine green (ICG) lymphography in patients with secondary lymphedema after breast cancer. Materials and Methods: This retrospective study was conducted on patients who underwent both lymphoscintigraphy and ICG lymphography for the evaluation of secondary lymphedema after breast cancer. The images were classified into type I - V according to the Arm Dermal Backflow (ADB) stage and modified MD Anderson Cancer Center (MDACC) stage on ICG lymphography and lymphoscintigraphy images on the basis of how lymphatic flow was preserved and how dermal back flow was extended. The correlation between scales was analysed. Results: A total of 47 patients were referred to our hospital for the evaluation of secondary lymphedema after breast cancer. There was no significant difference between lymphoscintigraphy severity scale and ADB stage (anterior and posterior). The lymphoscintigraphy severity scale and modified MDACC stage were significantly different. In the correlation analysis, lymphoscintigraphy and ADB (anterior) stage ( r  = 0.83), lymphoscintigraphy and ADB (posterior) stage ( r  = 0.86) and lymphoscintigraphy and modified MDACC stage ( r  = 0.85) exhibited very strong positive correlations. Intra-rater agreement between lymphoscintigraphy and ADB (anterior) stage and lymphoscintigraphy and ADB (posterior) was substantial ( κ =0.62 and κ =0.69, respectively) and fair ( κ  = 0.36) between lymphoscintigraphy and modified MDACC stage. Conclusion: Lymphoscintigraphy severity stage and ADB stage on ICG lymphography showed very strong positive correlation and substantial agreement. These two modalities can work synergistically to evaluate lymphedema severity.